COLOMBIA-FIDUAGRARIA-Sustainable low carbon development in the Orinoco Region - Barrios, Julián; Valencia Garcia, Jhon Brayan; Díaz, Nilton; Tapasco, Jeimar (2021)
Maps of emissions and mitigation by land use changes in the Eastern Plains of Colombia. Equations applied for the calculation of greenhouse gas emissions by land use change in the Orinoquia Region. (2021-09)